Synthesis techniques and advances in sensing applications of reduced graphene oxide (rGO) Composites: A review. (February 2023) - Ahmed, Aamir; Singh, Anoop; Young, Sheng-Joue; Gupta, Vinay; Singh, Maheshwary; Arya, Sandeep
Abstract: Reduced graphene oxide (rGO)-based hybridcomposites have been a popular area of study due to their outstanding optical, electrical, mechanical, and thermal capabilities. The thermal stability of rGO is very high and the total weight loss up to 800 °C is just 11 %. There are several applications for the rGO and its composites in a variety of sectors, from sensing to photocatalysis to upgrading batteries and supercapacitors. rGO is produced via various synthesis routes and this review briefly discusses the most popular production techniques. Reviewing recent findings on sensing applications of rGO and its composites, as well as discussing the difficulties encountered and the potential for improvement is a primary goal of this paper. rGO composite-based sensors have not reached the marketand are only confined to research laboratories. The proposed sensors must be mass-produced on an industrial scale to benefit real-world problems. The future holds great opportunities for rGO and its composites. rGO composite sensors will be commercially viable with further advancements in science and technology. The most anticipated and sponsored fields of study for rGO and its composites in the future are going to be energy harvesting and storage, environmental protection, biology, and medicine.